Leading under pressure: evaluating the decision-making style of NHL coaches - Trottier, K. (Sport, Business and Management, 2017)
Purpose: The purpose of this paper is to establish the optimal decision-making style in a fast-paced, complex, and dynamic environment. Design/methodology/approach